Visionnement de documents audiovisuels authentiques — Problématiques de contiguïté et d'interprétation culturelle - Laura M. Hartwell (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Using video documents to test foreign language comprehension implies a multimodal approach. Listening and observing are both actions incorporating multiple processes which function simultaneously, but at times, are in conflict with each other. This article examines the difficulties encountered by a portion of the 289 subjects taking a Cles-type oral comprehension test, either with or without the visual support. This analysis reveals that images do not always help to understand the document; in some cases they may cause interference. Written text such as captions or subtitles may transform a question based on oral comprehension to one of reading comprehension. Furthermore, the notion of contiguity is also essential. Given these findings, suggestions for improving listening comprehension evaluations are offered.